Spatio-temporal neighborhood impacts on internalizing and externalizing behaviors in U.S. elementary school children: Effect modification by child and family socio-demographics. (May 2017) - Humphrey, Jamie L.; Root, Elisabeth D.
Abstract: Increasing evidence from experimental and non-experimental research has shown that children residing in disadvantaged neighborhoods exhibit greater levels of internalizing and externalizing behaviors, above and beyond individual characteristics, and family or school contexts. Using the ECLS-K, a nationally representative, longitudinal survey of U.S. school children, this study examined direct neighborhood effects on internalizing ( N  =  14, 870; N  =  10, 610 ) and externalizing ( N  =  14, 960; N  =  10, 730 ) behaviors at the beginning and end of elementary school. Using IPTW propensity scores to mitigate selection bias and ordinary least squares regression, we examined direct neighborhood effects when children were 7 years old (1st grade) and when they were 11 years old (5th grade). We also examined neighborhood effect modification by child child race/ethnicity, sex, family structure, and family SES. Both the direct effect and effect modification models indicated that living in disadvantaged neighborhoods had no impact on either internalizing or externalizing behaviors at the beginning of elementary school (age 7). At the end of elementary school (age 11), we found small, yet significant direct neighborhood associations with effect sizes ranging from 0.12 to 0.18 standard deviations. The effect modification analysis revealed that being black (relative to white) was the strongest moderator of the relationship between neighborhood context and internalizing and externalizing behaviors in 5th grade, with effect sizes ranging from 0.27 to 0.59 standard deviations. Being Hispanic in high poverty neighborhoods was found to be protective for externalizing behaviors, suggesting the presence of the Hispanic health paradox. We also found, that in some neighborhood contexts, child sex, family structure, and family socioeconomic status amplified or dampened the effect of neighborhood, but only for externalizing behaviors. These results demonstrate the importance of age-dependent neighborhood effects and that children with different demographic profiles respond differently to the social contexts in which they are exposed. Highlights: Neighborhood effects on childhood behaviors were estimated at age 7 and 11. Effect modification-sex, race/ethnicity, married, SES was examined at age 7 and 11. No neighborhood effects at age 7; small direct neighborhood effects at age 11. Race/ethnicity was the largest moderator of neighborhood-behavior association. Sex, marital status, and SES impacted the way children responded to neighborhood.